Validasi Modifikasi Metode Volumetrik Penentuan Konsentrasi Sn (Timah) Pada Konsentrat Timah - Onek Gunawan; Nandya Tania; Yulismawati Yulismawati (Department of Chemistry - Universitas Bangka Belitung, 2021)
The analysis techniques for determining the concentration of Stanum (Sn) in Tin Concentrate has been developing since the 19th century. Various methods and analysis techniques are to find the most effective and efficient method enabling to achieve optimal results. In this study, a modification of the classic volumetric method that has been used includes modifications to the use of materials and tools in the analysis. In this study, validation and verification of the modified method was also carried out by determining the value of the parameters of Precision, Accuracy, Method of Detection Limit (MDL) and the Ruggedness and Robustness of the method and comparing the acceptability value based on the existing provisions. on the EURACHEM guide. After performing 25 tests using the NCS DC 35002 Certified Reference Material, it was revealed the value of the parameters for the Precision/Relative Standard Deviation (RSD) to be 0.21% (<0.5 CV Horwitz), the accuracy value is 99.9% with bias 0.06%, the MDL values for Minimum Detection Limit (MDL) and Limit of Quantification (LOQ) are 0.4% and 1.32%, respectively. The value of the ruggedness and robustness of the method was carried out by testing at different times and by different analysts and obtained RSD 0.22% (<2/3 CV Horwitz). From the values of the parameters obtained, it can be concluded that the modification of this method fulfills the acceptance value required by EURACHEM.